2020
DOI: 10.18805/ijare.a-484
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plant Spacing and Planting Model on Multiple Cropping of Red Chili (Capsicum annuum L.) and Shallot (Allium ascalonicum L.) under Saline Soil Conditions

Abstract: A field experiment was conducted from October 2018 to April 2019 at Sidomukti Village, Brondong Sub-District of Lamongan Regency, Province of East Java. The research was performed with the aim of examining and obtaining appropriate combinations of plant spacing and planting model for red chili (Capsicum annuum L.) and shallot (Allium ascalonicum L.) plants in saline soil conditions. The utilized design on this research was randomized block design. This research consists of 6 combinations that are repeated 4 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…An increasing trend was observed till the study periods of 180 DAP for plant. It is in agreement with observation in cabbage by Islam et al (2017); Aini et al (2020) in chilli. The interaction effect of spacing and days after planting represented significant variations.…”
Section: Plant Heightsupporting
confidence: 93%
“…An increasing trend was observed till the study periods of 180 DAP for plant. It is in agreement with observation in cabbage by Islam et al (2017); Aini et al (2020) in chilli. The interaction effect of spacing and days after planting represented significant variations.…”
Section: Plant Heightsupporting
confidence: 93%
“…The experiment was arranged in a randomized block design with five treatments and five blocks/replications, resulting in 25 experimental plots measuring 4 x 2 m, with a 1 m distance among the plots resulting in 12 red chili plants and 12 intercropping plants. Red chili and intercropping plants were planted at 60 x 40 cm spacing (Aini et al, 2020)Brondong Sub-District of Lamongan Regency, Province of East Java. The research was performed with the aim of examining and obtaining appropriate combinations of plant spacing and planting model for red chili (Capsicum annuum L.. All seedlings were prepared from certified healthy seeds in insect-proof boxes to ensure that all PepYLCIV infection was initiated in the field and brought in by its vector, B. tabaci.…”
Section: Intercropping Effect On Pepylciv Experimentsmentioning
confidence: 99%
“…Given the influence between the planting density and environmental factors on plant growth and production of shallots, it is necessary to pay particular attention to improve agricultural practices management (Askari-Khorasgani and Pessarakli 2019; Aini et al 2020). Bosekeng and Coetzer (2015) and Gogoi et al (2016) reported that increasing planting density treatment significantly affects plant growth, fresh bulb mass, bulb diameter, bulb firmness and production.…”
Section: Introductionmentioning
confidence: 99%